2018
DOI: 10.1159/000488637
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol and Peritoneal Protein Loss in Peritoneal Dialysis: A Double-Center Study

Abstract: Background/Aims: Peritoneal protein loss (PPL) is associated with cardiovascular disease and mortality in peritoneal dialysis (PD). Controversial results have been published about the effect of paricalcitol in PPL among PD patients. This study intends to analyze the relationship between paricalcitol and PPL in PD. Methods: In a retrospective study, prevalent PD patients were divided into 2 groups: “with paricalcitol” and “without paricalcitol”. X2-test, Student’s t test, Pearson correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…However, limited sample size and few associated factors considered in those studies might limit the implications. As proved in the current study with larger sample size, diabetes, higher D/P creatinine ratio, and lower residual renal creatinine clearance were independently associated with higher PPCl, which were consistent with some recent studies [4, 6, 8, 25-27]. These factors have been demonstrated as risk factors of increased mortality in PD population [28-31], which may partially explain the negative effects of higher PPCl on patients outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…However, limited sample size and few associated factors considered in those studies might limit the implications. As proved in the current study with larger sample size, diabetes, higher D/P creatinine ratio, and lower residual renal creatinine clearance were independently associated with higher PPCl, which were consistent with some recent studies [4, 6, 8, 25-27]. These factors have been demonstrated as risk factors of increased mortality in PD population [28-31], which may partially explain the negative effects of higher PPCl on patients outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Sánchez-Álvarez et al showed no change in PPL when using paricalcitol supplementation, but there was no control group enrolled in this study (63). Other studies, with larger study populations and controls, demonstrated a reduction of PPL with paricalcitol supplementation (23,28).…”
Section: Interventions To Reduce Peritoneal Protein Losses and Future Directionsmentioning
confidence: 89%
“…The results of investigations showed that the key to diminish PPL is not related to dialysis prescription, as once thought (3,43,58,59), and possible alternatives may include ACEIs and vitamin D therapies (1,28). The study of new therapeutic options is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paricalcitol also exerted other beneficial effects, like attenuation of in vitro MMT through Smads modulation [ 286 ]; impairment of oxidative stress; and activation of the NLRP3 inflammasome, a multiprotein complex that promotes IL-1β and IL-18 maturation [ 287 ]. Interestingly, a recent retrospective study in prevalent PD patients observed lower peritoneal protein loss in patients treated with paricalcitol [ 288 ]. Thus, paricalcitol acts as an anti-inflammatory agent that might improve peritoneal alterations in PD by mechanisms that could involve IL-17A modulation ( Figure 4 ).…”
Section: Pharmacological Interference With the Th17 Immune Responsmentioning
confidence: 99%